Dental And Oral Health In Patients With Hypertension Disease History - Fuad Fatkhurrohman; Hayyu Failasufa; Ayu Kristin Rakhmawati; Dwi Windu Kinanti Arti; Retno Kusniati (Maranatha Christian University, 2023)
Community Dentistry has a role to play in improving understanding and quality community dental with oral health through counseling and community dentistry services. Community dentistry services are services where operators must be able to recognize signs and symptoms of the possibility that patients are suffering from systemic diseases that can affect oral hygiene conditions. The aim of this writing is to report scientifically on community dentistry services based on the results of an assessment of health problems in the family. The respondent in this Community Dentistry activity was one of the residents assisted by RW 3, consisting of: mother IH, aged 46 years and brother NA, aged 12 years. Results and discussion: the dental health of the inmates, the condition of the patient's teeth and mouth was in poor condition where the results of the examination were poor OHI, there was bleeding on the gingiva, remaining roots, caries, and loss of several teeth due to caries. The results of Community Dentistry activities in assisted families, Mrs. IH had moderate oral hygiene with an OHI score of 6 before being given curative services in the form of scaling and root planing (SRP), after SRP was carried out, oral hygiene was good with an OHI score of 1.7. This means that there is a decrease in the OHI score after being given curative efforts in the form of SRP. Conclusion: Community dental services begin by preparing an intervention plan based on the results of an assessment of health problems in the family and will provide good intervention results and feedback to the patient's family who cooperate in following input and suggestions by the dentist and other health workers.